On the Soret effect in binary nonstoichiometric oxides kinetic demixing of cuprite in a temperature gradient - Timm, H.; Janek, Jürgen; Justus Liebig University Giessen (My University, 2005)
The Soret effect in nonstoichiometric copper(I)-oxide (cuprite, Cu2-deltaO) has been studied experimentally by means of non-isothermal solid state galvanic cells (thermocells) under different boundary conditions. At high temperatures and high oxygen activities, copper metal migrates down the temperature gradient and a gradient in the nonstoichiometry is established under stationary conditions. The heat of transport of copper metal is determined as Q*Cu is equivalent to 180 kJ/mol at a temperature of 1000 °C and at an oxygen activity of log aO2=-2.95. This result agrees with recent theoretical simulations of the heat of transport of atoms migrating via a vacancy mechanism. These predict a positive sign of the heat of transport and a considerably larger value than the activation energy for the atomic jumps.
Keywords: ddc:540